From peripheries to neighbourhoods: measuring urban insertion of social housing projects - Nascimento Neto, Paulo; de Paula, Marina Quirino Luxi; Araujo, Agnes Silva de; Oliveira, Everton Narciso de (TeMA - Journal of Land Use, Mobility and Environment, 2024)
The past two decades have witnessed a notable increase in affordable housing production across Latin America, along with persistent challenges regarding habitability and access to urban amenities. At the same time, there has been a shift in urban dynamics, characterised by the diversification of peripheries and the emergence of sub-centralities, challenging conventional notions of urban marginalisation. It underscores the need for a deeper understanding of urban insertion as the attention moves from macro-scale segregation to micro-scale analysis. Amidst this context, urban insertion remains a subject of dispute and ambiguity within the literature, often conflated with peripheralisation and segregation. Addressing this gap, we advance toward a concept of urban insertion, proposing an analytical framework that integrates multiple criteria from diverse disciplinary perspectives. This framework was empirically validated in the metropolitan area of Curitiba (Brazil) by analysing 55 social housing developments constructed over the past decade. The findings yield valuable insights and pragmatic guidelines for evaluating urban insertion and informing policy decisions in similar contexts.